The impact of the policies directed to the yerba mate San Pedro, Misiones, Argentine Republic, microproducers, depends on the pertience and efficiency of the programs - Godoy, Antonia Elisabeti (2021)
Fil: Godoy, Antonia Elisabeti. Universidad Nacional de Misiones. Facultad de Ciencias Económicas; Argentina.